1965
DOI: 10.1530/acta.0.0480348
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function and Kidney Size Following Hypophysectomy in Man

Abstract: Measurements of glomerular filtration rate (GFR) and renal plasma flow (RPF) were performed in close connection with roentgenographic estimation of kidney size, before and after hypophysectomy, in 10 patients (four cases of metastatic mammary carcinoma, five cases of diabetic retinopathy and one case of acromegaly). Hypophysectomy was regularly followed by a decrease in GFR and RPF. In most cases, a reduction in the roentgenographic kidney size was also observed. However, the changes in the roentgenogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…There is substantial evidence that growth hormone affects renal function (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Growth hormone excess, whether from endogenous hypersecretion or chronic exogenous administration, has been associated with an increase in renal blood flow, glomerular filtration rate (1)(2)(3)(4)(5)(6), and increased levels of serum phosphate (7-9, 13-15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is substantial evidence that growth hormone affects renal function (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Growth hormone excess, whether from endogenous hypersecretion or chronic exogenous administration, has been associated with an increase in renal blood flow, glomerular filtration rate (1)(2)(3)(4)(5)(6), and increased levels of serum phosphate (7-9, 13-15).…”
Section: Introductionmentioning
confidence: 99%
“…Brush border membrane vesicles prepared from the renal cortex of dogs treated with growth hormone for 3 d had an increase in sodium-dependent phosphate uptake (16). Likewise, hypophysectomized animals had a reduction in renal blood flow and glomerular filtration rate, effects reversed by growth hormone administration (1,10,11). Selective growth hormone deficiency, induced by administration ofa synthetic peptide antagonist to growth hormone releasing factor, resulted in a reduction in glomerular filtration rate and increased the fractional excretion of phosphate ( 12).…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations used in this paper: HCT, hematocrit; IGF, insulin-like growth factor; MABP, mean arterial blood pressure; PAH, para-aminohippurate; RPF, renal plasma flow rate; RVR, renal vascular resistance. mone levels have increased RPF and GFR (2). After pituitary ablation, RPF and GFR fall to normal; this fall precedes the reduction in kidney size (2).…”
Section: Introductionmentioning
confidence: 99%
“…mone levels have increased RPF and GFR (2). After pituitary ablation, RPF and GFR fall to normal; this fall precedes the reduction in kidney size (2). Moreover, injections of growth hormone in man increase RPF and GFR.…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason why we evaluated changes in the GFR in acromegalic patients who have achieved remission by surgery alone. This reduction in the GFR after hypophysectomy in patients with acromegaly was reported as early as 1965 (25). Recently, Sze et al reported a decrease in the GFR after transsphenoidal surgery in 20 cured and four non-cured patients with acromegaly (26).…”
Section: Discussionmentioning
confidence: 93%